The energy problem - Stein, Richard S. (World Scientific, 2011)
Most scientists now believe that carbon dioxide concentrations in the atmosphere are rapidly increasing, and that emissions from the burning of fossil fuels is a principal cause. Thus, it is probable that this will affect the climate and lead to global warming. This book familiarizes the non-specialist with alternative sources of energy, pointing out their advantages and disadvantages. The appropriate principles of physics and chemistry involved in each alternative will be presented in an easily digestible manner. The book seeks to better inform the public about specific actions that need to be taken in order to better combat energy problems, and reduce climate change. -- Back Cover